Extending the reach of science – Talk in plain language - Cassie Sedgwick (Elsevier, 2021)
There has been increasing interest by the general public to read and share mainstream medical and scientific literature. Consequently, more and more medical journals are adopting strategies to make complex literature more accessible to the lay public. One such strategy is the creation of so called “lay summaries”. The benefits of lay summaries can include wider dissemination of knowledge, and is increasingly being recognized as a unique expertise by authors. While on the surface, it may seem to be an easy task to translate scientific literature into a lay summary. However, occasionally authors who are experienced in communicating complex information to a peer group, may struggle with translating their work to an audience with limited medical or scientific background. The objective of this review is to discuss strategies that scientific writers may consider to better facilitate translating scientific literature into lay summaries.